1999
DOI: 10.3171/jns.1999.91.3.0459
|View full text |Cite
|
Sign up to set email alerts
|

Oxyhemoglobin-induced apoptosis in cultured endothelial cells

Abstract: Oxyhemoglobin decreased cell density in a concentration- and time-dependent manner. Analysis of DNA showed a pattern of internucleosomal cleavage characteristic of apoptosis (DNA ladder). Transmission electron microscopy demonstrated condensation of nuclei and apoptotic bodies in OxyHb-treated endothelial cells. Western blotting with the PARP antibody revealed that the 116-kD PARP was cleaved to the 85-kD apoptosis-related fragment. These results for the first time demonstrated that the OxyHb induces apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…The degree of cytotoxicity was related to the concentrations of Hb over time (72). Other studies have shown similar effects associated with DNA damage and apoptosis (73,74).…”
Section: Hb Toxicity Towards Endothelial Cellsmentioning
confidence: 60%
“…The degree of cytotoxicity was related to the concentrations of Hb over time (72). Other studies have shown similar effects associated with DNA damage and apoptosis (73,74).…”
Section: Hb Toxicity Towards Endothelial Cellsmentioning
confidence: 60%
“…It has also been shown that oxyhemoglobin can induce apoptosis in cultured endothelial cells, possibly through free radical damage to the endothelial vessel wall tissue. 9 The temporal pattern of edema formation after infusion of lysed or packed erythrocytes is similar to the pattern of BBB disruption. 3 A second mechanism that might contribute to edema development after erythrocyte lysis is direct damage to neurons and astrocytes involved in maintaining extracellular homeostasis.…”
Section: Discussionmentioning
confidence: 72%
“…Damage to the vascular endothelium may be because of oxidative stress perpetuated by iron (Ogihara et al, 1999;Wu et al, 2003Wu et al, , 2002 and furthermore the administration of iron chelators attenuates edema after intracerebral hemorrhage (Huang et al, 2002).…”
Section: Heme Oxygenase As Modulator Of Neural Injurymentioning
confidence: 99%